Pengembangan E-comic Berbasis Problem Based Learning (PBL) pada Pembelajaran Pendidikan Pancasila Kelas IV SD Materi Negaraku Indonesia - Akbar, Mohamad; Hidayat, Otib; Sagita, Julius (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Balikpapan, 2025)
This research and development aims to produce learning media products in the form of E-comic Based Problem Based Learning in Class IV Elementary School Pancasila Education learning. The results of this product are used as a support for classroom learning activities, namely becoming an interesting and appropriate learning medium. This research and development refers to the Hannafin & Peck model which consists of 3 stages, namely Needs assesment, Design, Develop and Implementation. The results of product development after carrying out expert review by media experts they get a suitability percentage of 98.67%, by material experts get a 89.33%, by language experts get 98% which shows the media has very good qualifications. Instructional Media e-comic A trial was also carried out on class IV B of SDN 03 Rambutan with the results being at the trial stage one to one got a percentage of 91.56%, at the trial stage small group got a percentage of 98.1%, at the trial stage field test get a percentage of 92.97%. The test results show the media E-comic Based Problem Based Learning in learning Pancasila Education Class IV Elementary School received very good qualifications and is suitable for use in learning Pancasila Education.